BUSINESS PHILOSOPHY OF ELIYAHU M. GOLDRATT: THE GOAL: A PROCESS OF ONGOING IMPROVEMENT - Maraimova Kamola Shuhratovna; Xasanov Ne’matillo Farxodjon o’g’li; Xamidov Aziz Dexkonboyevich (Ecominds Press, 2025)
Imagine the following: your factory appears to be a textbook success - people are all remaining at work, machines are working, and the orders continue to come in. But the real show‑down? Late timelines, budget bloating and unreasonable pressure. It is a case that is too close to the heart when it comes to product manufacturing. Goldratt’s 1984 manufacturing The Goal is full of such headaches, and that is what this novel, a detective mystery and philosophy combination becomes so sharply and allows you to experience the mess first-hand. This is not a business textbook that is dry. It is a handbook you can use in practice without any difficulties when you are in classes or even working part-time.